Kritik Sastra Semiotik Terhadap Cerita Rakyat Kisah Dua Penjaga Gunung - Tika Agustin, Veran; Novi Setiani; Farel Tulus Rohmat; Ani Diana (Jurnal Multidisiplin Indonesia, 2023)
Literary works are extraordinary images framed by the creative mind of an inventive and useful creator. One way that can be used to focus attention on a scientific work is through literary criticism. This research aims to appreciate a literary work in semiotic literary criticism of the folk tale The Story of the Two Mountain Guards. The study that researchers will use in this research is semiotic literary criticism using descriptive qualitative analysis methods. Based on data analysis, in the song the researchers found 4 icons, 4 indexes and 2 symbols.